2018
DOI: 10.1089/scd.2017.0195
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Derived Directly from Adipose Tissue

Abstract: Neural stem cells (NSCs) are characterized as self-renewing cell populations with the ability to differentiate into the multiple tissue types of the central nervous system. These cells can differentiate into mature neurons, astrocytes, and oligodendrocytes. This category of stem cells has been shown to be a promisingly effective treatment for neurodegenerative diseases and neuronal injury. Most treatment studies with NSCs in animal models use embryonic brain-derived NSCs. This approach presents both ethical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…However, as we all know, the unfavorable accessibility combined with ethical issues of human NSCs have long restricted their wide clinical use. This problem could be potentially solved if we could develop an easy way to obtain NSC/neural progenitor cells (NPCs) from more accessible stem cell sources [19][20][21][22] , such as ADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, as we all know, the unfavorable accessibility combined with ethical issues of human NSCs have long restricted their wide clinical use. This problem could be potentially solved if we could develop an easy way to obtain NSC/neural progenitor cells (NPCs) from more accessible stem cell sources [19][20][21][22] , such as ADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The amount described is much higher than the used in this study, which was only 2 × 10 4 cells/mL. Although the sources of formation were different, the present study does not use growth factors, and the number of cells necessary to produce neurospheres was lower [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the present study used conventional media and no supplementation in the culture medium to produce neurospheres from undifferentiated MSCs, regardless of MSC-WJ or MSC-UCB, only the NFBX was coating the culture flasks before hMSCs plating was conducted. The NFBX method made this study more economical, practical, and without the drawbacks of inductions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments showed that adipose-derived stem cells could act as a possible source of brain progenitor cells and that they are clinically important in neurological applications (36). Moreover, their efficiency can be improved by the addition of growth factors to media formulations, as this would enhance the efficiency of differentiation of adipose tissue into neural stem cells (37).…”
Section: Discussionmentioning
confidence: 99%